Application of fuzzy logic to simulation of rainfall in Kerayong River catchment / Kamsiah Abdul Wahab - Abdul Wahab, Kamsiah (2009)
Short term rainfall characteristics of Kerayong River catchment, a tributary of Klang River were analysed in this research. As the urbanisation process and the population increased in this catchment is inevitable, therefore knowledge on rainfall characteri stics is necessary and useful in designing future drainage system. There are four rainfall and five stage monitoring stations established in this catchment. The rainfall stations are equipped with data logger of 0.5 mm tipping bucket resolution and record the data based on event mode. Time Dependent Data Analysis (TIDEDA) program is used by Department of Irrigation and Drainage (DID) Malaysia to read and edit the data for further analysis. The available data of Kerayong River catchment were beginning from year 2001 and 2002 which continuous data were available for all stations. The spatial and temporal distribution for Kerayong River catchment is studied by plotting the storm event at one minute interval. The analysis shows that the daily rainfall temporal pattern for the year 2001 and 2002 was found to be relatively similar to all stations. However the magnitude of rainfall intensity varies considerably at short time intervals. The result shows that there are missing data occur during the thunderstorm at Kg. Cheras Barn station from 15th January to 16th May 2003 . The missing data are related to the malfunctioning of the instruments and vandalism. Therefore, the potential of fuzzy logic modeling i.e. Fuzzy Rule Based Model (FRBM) and Normal Ratio Method (NRM) for filling the missing data at Kg. Cheras Barn was investigated. A total of 420 daily rainfall values i.e. data for year 2001 and 2002 are employed to construct the FRBM. The numbers of data sets are selected in randomly and divided into training and verification sets. The rules are adopted from the available daily rainfall record with the simple assumption.